Case Report: Clinical management of a severe DBA patient with a novel RPS19 mutation - Zhou, Junfen; Zhong, Jiayi; Zhao, Yisha; Mo, Miaojun; Chen, Xianbo; Zhou, Huangjia; Zhang, Luya; Lin, Li; Zhang, Yichi; Tao, Xiaohong; Mao, Xianhua; Li, Haiting; et al. (Frontiers in Pediatrics, 2025)
Diamond-Blackfan anemia (DBA) is a rare congenital bone marrow failure disorder characterized by defective erythropoiesis, typically caused by mutations in ribosomal protein (RP) genes, most commonly RPS19. It usually presents in early infancy with severe anemia, growth retardation, and an increased risk of congenital malformations and malignancies. However, cases of DBA leading to severe anemia and shock are exceedingly rare. This case report describes a life-threatening presentation of DBA in a 56-day-old female infant who presented with severe anemia and shock. The infant was admitted with a 2-day history of poor feeding and persistent crying, accompanied by hypothermia (34.4°C), unresponsiveness, and profound pallor. Initial laboratory findings revealed critical anemia (hemoglobin 18 g/L) and severe metabolic acidosis (pH 6.61, base excess −36.06 mmol/L). Hemodynamic instability, including undetectable blood pressure and prolonged capillary refill time, indicated shock. Immediate interventions, including volume expansion with normal saline, correction of acidosis with sodium bicarbonate, and packed red blood cells (PRBCs) transfusion, stabilized the infant. Genetic testing identified a de novo heterozygous mutation in the RPS19 gene (c.3G > T), confirming the diagnosis of DBA. Over the course of a 1-year follow-up, the infant required regular blood transfusions at approximately 4-week intervals to sustain hemoglobin levels within the range of 69–86 g/L. Growth retardation and poor appetite were observed, consistent with the known complications of DBA. This case highlights the importance of early recognition and aggressive management of severe anemia in infants, particularly in the context of DBA, to prevent life-threatening complications such as shock and metabolic acidosis. The role of genetic testing in confirming the diagnosis and guiding long-term management is emphasized. This report also reviews the literature on DBA, focusing on the pathophysiology of anemia, the association between RPS19 mutations and clinical phenotypes, and the challenges of managing transfusion-dependent patients. The findings underscore the need for a multidisciplinary approach to DBA, including regular monitoring for complications such as iron overload, growth retardation, and malignancy risk. Early genetic counseling and tailored therapeutic strategies are crucial for improving outcomes in this rare and complex disorder.